2010
DOI: 10.1007/s13238-010-0072-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of themicrobial lipopeptide on tumor cell lines: apoptosis induced by disturbing the fatty acid composition of cell membrane

Abstract: Microbial lipopeptides play an important role in apoptosis induction of tumor cells. However, there is little knowledge about the relationship between apoptosis induction and membrane fatty acids. The present study focused on the effects of lipopeptides produced by Bacillus subtilis HSO121 on Bcap-37 cell lines. 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl (MTT) colorimetric assay and surface tension measurements, showed that the critical micelle concentration (CMC) was a critical level for the inhibitory activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 46 publications
2
37
0
1
Order By: Relevance
“… Leukemia: B. subtilis natto T-2 derived surfactin exhibited toxicity in human K562 leukemia cells at different concentrations (2–62 μM) for 24–48 h. Surfactin inhibited the growth of K562 cells in the 24–48 h treatment period at IC 50 values ranging between 10–20 μM [ 52 ]. Hepatocellular carcinoma: The cytotoxic effect of surfactin on hepatocellular carcinoma was investigated and surfactin-like lipopeptides were found to strongly inhibit the cell viability of human Bel-7402 hepatoma cells, with IC 50 of 35 ± 12 μM [ 53 ]. Wang et al [ 54 ] found that surfactin induced apoptosis in the HepG2 cells via the ROS/ERS/Ca 2+ -mediated ERK pathway.…”
Section: Effect Of Bs On the Immune Systemmentioning
confidence: 99%
See 3 more Smart Citations
“… Leukemia: B. subtilis natto T-2 derived surfactin exhibited toxicity in human K562 leukemia cells at different concentrations (2–62 μM) for 24–48 h. Surfactin inhibited the growth of K562 cells in the 24–48 h treatment period at IC 50 values ranging between 10–20 μM [ 52 ]. Hepatocellular carcinoma: The cytotoxic effect of surfactin on hepatocellular carcinoma was investigated and surfactin-like lipopeptides were found to strongly inhibit the cell viability of human Bel-7402 hepatoma cells, with IC 50 of 35 ± 12 μM [ 53 ]. Wang et al [ 54 ] found that surfactin induced apoptosis in the HepG2 cells via the ROS/ERS/Ca 2+ -mediated ERK pathway.…”
Section: Effect Of Bs On the Immune Systemmentioning
confidence: 99%
“…Wang et al [ 54 ] found that surfactin induced apoptosis in the HepG2 cells via the ROS/ERS/Ca 2+ -mediated ERK pathway. Cervical cancer: Lui et al [ 53 ] investigated the effect of surfactin on cervical cancer in HeLa cell line. The IC 50 dose of surfactin at 16–48 h was ranged between 86.9–50.2 µM [ 53 ].…”
Section: Effect Of Bs On the Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…A surfactina inibiu as vias de sinalização fosfatidilinositol-3--quinase/serina-treonina quinase (PI3K/Akt) e proteína quinase ativada (MAPK) em células MCF-7 e reduziu a insaturação do ácido graxo na membrana da célula que conduz a apoptose celular em células de câncer de mama Bcap-37. 38 A surfactina purificada do B. natto foi relatada pela primeira vez por possuir efeitos antitumorais em células do carcinoma de Ehrlich, e a surfactina purificada a partir da linhagem TK-1 inibiu células do câncer de mama MCF-7. A surfactina induziu a apoptose, e o ciclo celular parou na fase G 2 /M em células de câncer de mama MCF-7 como resultado da clivagem da caspase-3 em células MCF-7.…”
Section: 11unclassified